Peran Kecerdasan Emosi terhadap Quarter Life Crisis pada Mahasiswa Tingkat Akhir - Ridha Amelia Rivanda; Fatma Nofriza (Departement of Mathematics Education, 2024)
Final-year students often feel anxious about career prospects, indecision, being stuck in difficult situations, and uncertainty about the next steps after graduation, which negatively impacts their emotional state. This phenomenon is known as quarter-life crisis. The aim of this study is to determine the role of emotional intelligence (X) on the quarter life crisis (Y). This research uses a correlational quantitative method with a sample of 63 students aged between 20-25 years. Data collection was conducted using instruments in the form of a Likert scale for the quarter-life crisis and emotional intelligence scales. The sampling technique used was simple random sampling. Data were analyzed using Pearson’s product-moment correlation with the assistance of SPSS 26.0 for Windows. The correlation test results showed a value of -0.500 wich is significant. This value indicates a negative correlation between emotional intelligence and the quarter-life crisis, meaning that individuals with high emotional intelligence tend to experience lower quarter life crises. Conversely, individuals with low emotional intelligence tend to experience a higher quarter-life crisis.